Behavioural Responses of the Indian Desert Gerbil, Meriones Hurrianae Towards Conspecific and Interspecific Sebum Odour - Idris, Mohd (Annals of Arid Zone, 2016)
Live Indian desert gerbils, Meriolles huriianae, trapped from sandy habitat, were exposed to conspecific and interspecific sebum odours of M. hurriallae and M. unguiculatus, respectively,' in multiple choice tests. The experimental gerbils were released in the middle of the glass cage (90x3Ox30 cm) and its behavioural responses like sniffing, licking, scent marking, urination and defecation were observed. Exposure of conspecific and interspecific sebum odours in five combinations to M. hurrianae indicated that these gerbils perceive not only conspecific odour of the ventral sccnt marking gland but also . that of another species which is not sympatric i.e. M. unguiculatus. preferred(P< O.05) uni-sex odour, even that of M. unguiculatus, and also enhanced its own scent marking frequency in the presence of scent marking gland odours of, the strange gerbils.